2018
DOI: 10.1016/j.jhin.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of antimicrobial stewardship programmes in children: a systematic review

Abstract: Abstract:The United Nations and the World Health Organization have designated antimicrobial resistance (AMR) as a major health priority and developed action plans to reduce AMR in all healthcare settings. Establishment of institutional antimicrobial stewardship programmes (ASPs) is advocated as a key intervention to reduce antibiotic consumption in hospitals and address high rates of multi-drug resistant (MDR) bacteria. We searched PUBMED and the Cochrane database of systematic reviews (1/2007-3/2017) to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 22 publications
(22 reference statements)
2
61
0
6
Order By: Relevance
“…This is the first systematic scoping review analysing the implementation of ASPs in pediatrics globally, in both inpatient and outpatients settings. Previously, two systematic reviews had been conducted which did not include ASPs intervention in outpatient settings, with Smith et al [154] limited to inpatient interventions in the USA and Da Silva et al [155] limited to general pediatric wards and PICU.…”
Section: Main Findingsmentioning
confidence: 99%
“…This is the first systematic scoping review analysing the implementation of ASPs in pediatrics globally, in both inpatient and outpatients settings. Previously, two systematic reviews had been conducted which did not include ASPs intervention in outpatient settings, with Smith et al [154] limited to inpatient interventions in the USA and Da Silva et al [155] limited to general pediatric wards and PICU.…”
Section: Main Findingsmentioning
confidence: 99%
“…Effectiveness of ASPs in paediatric inpatient populations other than neonates has been summarised by two systematic reviews 24 25. The first review identified nine studies in various US paediatric inpatient settings,24 the second review focused on paediatric intensive care, and identified nine studies from the US, Germany, Indonesia and Singapore 25. All studies reported reductions in the use of antibiotics overall and broad-spectrum/restricted antibiotics in particular 25.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Literature supporting ASP interventions in critically ill neonates and children are especially limited, and extrapolation of published PAF success in a specific institution's ICU may be difficult due to differences in patient populations served and institutional microorganism resistance patterns. 22 Further exploration of the factors impacting the success of stewardship in critically ill children are needed. Interestingly, we did not find that any specific marker of infection (eg, procalcitonin, CRP, fever), antimicrobial, or severity of illness (eg, LOS, ICU LOS, need for mechanical ventilation) impacted adherence to PAFR.…”
Section: Discussionmentioning
confidence: 99%